In vitro Propagation of orchid (Dendrobium ovatum (L.) Kraenzl.) through Somatic Embryogenesis (Plant Tissue Culture and Biotechnology, 2022)
An efficient in vitro regeneration protocol through somatic embryogenesis was established from longitudinally bisected protocorm (lTCL) of an endangered orchid Dendrobium ovatum. The efficiency of EC and SEs from the protocorms significantly relied on the concentration of PGRs. MS medium supplemented with TDZ (1.0 mg/l) induced optimum of EC (31.8%) and SEs (28.1/explant). Similarly, ZEA (0.5 mg/l) induced EC (27.6%) and SEs (17.1/explant). The combined treatment of TDZ (1.0 mg/l) and NAA (0.5 mg/l) resulted in the maximum induction of EC (58.6%) and SEs (39.8/explant) in an upright incubated explant. In another combined effect of ZEA (1.0 mg/l) and NAA (0.5 mg/l) induced EC (43.8%) and SEs (24.3/explant), whereas the combination of BAP (0.5 mg/l) and NAA (0.5 mg/l) produced EC (34.4%) and SEs (16.8/explants). The induced EC and SEs where healthier on medium containing TDZ + NAA than on the medium containing ZEA+NAA and BAP+NAA. The orientation of lTCL explants seemed to interact with position to affect the morphogenesis. The lTCL explants incubated in the upright orientation induced higher percentage of EC and a greater number of SEs/explants (EC-58.6% and SEs-39.8/explants) than that in the inverted orientation (EC- 16.4% and SEs-9.1/explants) irrespective of the PGRs. The SEs developed from the EC and the intermediate stage of PLBs were finally differentiated into plantlets. About 89% of plantlets were successfully acclimatized in the green house conditions.Plant Tissue Cult. & Biotech. 32(1): 53-66, 2022 (June)